2022
DOI: 10.3390/met12071201
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Structure of Electrolytically Synthesized Tin Dendritic Nanostructures

Abstract: The formation of tin dendritic nanostructures by electrolysis from the alkaline electrolyte has been investigated. Morphology and structure of Sn dendrites produced applying both potentiostatic and galvanostatic regimes of the electrolysis are characterized by SEM and XRD, respectively. Depending on the applied cathodic potentials, three types of Sn dendrites were obtained: (a) needle-like and spear-like, (b) fern-like, and (c) stem-like dendrites. The very branchy dendrites with branches of the prismatic shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…An alternative route for producing tin powder is the electrolysis method . This method has several advantages: it can produce nanopowder particles, requires relatively simple equipment, and produces high-purity powder. , In contrast to the atomization method, there is no risk of lead fume emissions since this technique does not use a lead-bearing molten tin ingot for producing tin powder.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…An alternative route for producing tin powder is the electrolysis method . This method has several advantages: it can produce nanopowder particles, requires relatively simple equipment, and produces high-purity powder. , In contrast to the atomization method, there is no risk of lead fume emissions since this technique does not use a lead-bearing molten tin ingot for producing tin powder.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the tin powder deposits obtained under the entire specified overpotential variations were dendritic in morphologies. Nikolic et al (2022), 6 reported that the morphology and structure of Sn dendrites produced by applying both potentiostatic and galvanostatic regimes of the electrolysis in the alkaline hydroxide electrolyte depended on the applied cathodic potential, the current density, and the polarization characteristic during the electrolysis. Three types of Sn dendrites were obtained depending on the applied cathodic overpotential, namely needle-like, fern-like, and stem-like dendrites.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The morphologies of metal or alloy deposits can be easily regulated by the choice of parameters and regimes of the electrodeposition [31,34]. In our previous work, it was shown that Sn's morphology and structure depends on the electrolysis conditions, which can produce Sn dendrites of various shapes and degrees of ramification [35]. In addition, all types of Sn dendritic particles had nanostructural characteristics [35].…”
Section: Introductionmentioning
confidence: 99%